Controllable Synthesis and Luminescence Properties of Zn2GeO4 : Mn2+ Nanorod Phosphors. Issue 39 (15th October 2021) - Cui, Zheng; Deng, Guowei; Wang, Ou; Luo, Xiaolan; Li, Zhonghui; Yang, Min; Cheng, Shaoheng; Liu, Xiaoyang
Abstract: In this study, color tunable phosphors (Mn 2+ ‐doped Zn2 GeO4 ) were successfully synthesized by a facile microwave hydrothermal process with H2 O as solvent. Crystal field modulation and band gap doping by Mn 2+ substitution for Zn 2+ realizes color tunable Mn 2+ emission from 424 to 535 nm. Mn 2+ ‐doping on the phase and size transition of Zn2 GeO4 nanocrystals was discussed, and a possible Zn2 GeO4 : xMn crystal growth mechanism is discussed. Photoluminescence (PL) spectra indicate that the d‐d transition of manganese ions ( 4 T1 → 6 A1 ) corresponds to a strong green emission of Zn2 GeO4 : xMn phosphors. Abstract : Zn2 GeO4 :Mn 2+ nanorods was synthesized by one‐step microwave hydrothermal synthesis. The color tunability of Mn 2+ luminescence in the range of 424∼535 nm was realized by crystal field modulation and band gap doping of Mn 2+ instead of Zn 2+ . The Mn 2+ ‐doped Zn2 GeO4 phosphor shows green light emission with better color purity and proper intensity due to the d‐d transition ( 4 T1 → 6 A1 ) of Mn 2+ ions.